Triangulation Framework for Local Service Delivery - Allan S. Layug (Philippine Institute for Development Studies (PIDS), 2009)
How should local service delivery of public goods and services be improved for desirable development outcomes? This paper attempts at answering this question by providing a framework for improving local service delivery. It argues that improving local service delivery is a function of triangulating delivery of any public goods and services through their policy, institutional, and financial characteristics; zeroing in on their interdependence and normative dimensions; the effectiveness of institutions and capabilities and productivity of their actors; and the role of governance against the backdrop of development constraints and supported by opportunities for reforms. It further argues that institutions and their actors take the primordial role in improving local service delivery especially in cases of policy gaps and financial inadequacies. Corollary argument is that governance - both institutional and democratic - is the key in helping catalyze institutional change and improving service provision to achieve such goals as quality of life, empowered citizenry, and responsive leadership based on normative entitlements. The values (rights, equity, quality, and sustainability) and elements/principles of governance (efficiency, participation, transparency, accountability, and predictability) both lay the groundwork for delivering goods and services, as well as serve as indicators in assessing local service delivery. In other words, improving local service delivery is a function of the triangulation of policy, institutions, and finance within value-based and principle-oriented governance framework.
Keywords: 330; governance; decentralization; development; institutions; local service delivery; triangulation; Dezentralisierung; Kommunale Dienstleistung; Governance-Ansatz; Philippinen